The effect of 25‐hydroxyvitamin D3 and phytase inclusion on pig performance, bone parameters and pork quality in finisher pigs. Issue 5 (5th July 2018) - Duffy, Sarah K.; Kelly, Alan K.; Rajauria, Gaurav; Clarke, Louise C.; Gath, Vivian; Monahan, Frank J.; O'Doherty, John V.
Abstract: The objective of this study was to investigate the effects of supplementing both phytase and 25‐hydroxyvitamin D3 (25‐OH‐D₃) on pig performance, nutrient digestibility, carcass characteristics, bone parameters and pork quality in finisher pigs. The experimental design was a 2 × 2 factorial comprising of four dietary treatments. One hundred and twenty pigs (60 male, 60 female) were blocked according to live weight and sex and allocated to the following dietary treatments: low P (4.81 g/kg) diet (basal) (T1); low P diet + phytase (T2); low P diet + 25‐OH‐D₃ (T3) and low P diet + phytase + 25‐OH‐D₃ (T4). Pigs supplemented with phytase had a lower average daily feed intake (ADFI) (2.45 kg vs. 2.59 kg; p  < 0.05) and lower feed conversion ratio (FCR) (2.74 kg/kg vs. 2.85 kg/kg; p  <   0.05) compared to pigs offered the nonphytase diets. Pigs offered phytase diets had a higher ( p  <   0.05) coefficient of apparent total tract digestibility (CATTD) of ash, phosphorous (P) and calcium (Ca) compared with pigs offered the nonphytase supplemented diets. Pigs offered the 25‐OH‐D3 diets had a higher CATTD of N and ash. Pigs offered the phytase diets had increased ( p  <   0.05) bone DM, ash, Ca, P and density compared to the nonphytase diets. There was a significant interaction ( p  <   0.05) between phytase and 25‐OH‐D3 on cook loss. Pigs offered 25‐OH‐D3 had increased cook loss over the basal diet; however, there was no effect on cook loss when phytase and 25‐OH‐D3 were offered in combination compared to the phytase only diet. Pigs offered 25‐OH‐D3 exhibited higher ( p  <   0.05) Warner Bratzler shear force values and lower ( p  <   0.05) pork lightness ( L *) surface colorimeter values. In conclusion, there was no benefit to offering a combination of phytase and 25‐OH‐D3 on pig performance, bone parameters or pork quality.